Network Scan Detection Simulation - Paulauskas, N.; Garšva, E.; Skudutis, J. (Elektronika ir Elektrotechnika, 2009)
The network scan detection provides information about the attempts of attackers to determine servers and to prevent potential trials to compromise them. In the work the model for simulation of the network scanning and its detection using the stochastic activity network and their simulation tool Mobius is proposed. The model allows operative evaluation of the influence of simulated computer system parameters on the scan detection efficiency and proper configuration of the intrusion detection system. The results of the horizontal scan simulation are presented. The IDS parameters having the highest influence on the intrusion detection performance for a specific case have been determined. Ill. 3, ref. 5 (in English; summaries in English, Russian and Lithuanian).